Perubahan kontruksi sosial dalam pembagian kerja domestik: Studi hubungan antara suami istri keluarga modern - Venny Pratisiya; Aldea Pantes; Sasmita Fahira; Dahniar Th Musa; Annisa Rizqa Alamri; Mutmainnah Mutmainnah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2023)
The aim of this research is to analyze changes in social construction and the division of domestic labor in modern households in an urban environment. Social construction, which involves norms, values and social expectations, plays an important role in the division of domestic labor in the family. Factors such as cultural traditions, religion, internalized gender roles and influences from the social environment contribute to the formation of social construction. The research method used is qualitative literature study, researchers analyze and collect scientific articles, journals, books and other sources relevant to this research topic. The theory used is social construction theory developed by Peter L. Berger and Thomas Luckmann. This theory is used to identify how norms, values and social roles in domestic work are constructed, internalized and changed in the context of the modern family. The results of this research show that stereotypical gender roles and behavioral expectations for women in domestic work burden women in the unequal division of work between husband and wife. Apart from that, this research also shows that there are various significant changes in the social construction related to domestic work in modern families, such as shifts in gender roles and awareness of gender equality. One of the factors that can influence a husband and wife or a modern family to adopt an egalitarian division of labor is education, work experience and individual values.